THE COMMUNICATION STRATEGY OF THE CIREBON CITY COMMUNICATION, INFORMATION, AND STATISTICS AGENCY (DKIS) IN EMPOWERING SMES THROUGH THE "MILM KAMPUNG FESTIVAL" PROGRAM WITH THE "DAPUR NGEBUL " THEME - Swastiningsih Swastiningsih (Journal of Social Political Sciences, 2023)
This research investigates the role of communication strategies and their application in the context of the "Village Film Festival" in 2023, themed "Smoky Kitchen," with the aim of promoting community products, enhancing social welfare, and fostering unity amidst global challenges and competition. The methodology thoroughly analyzes communication strategy formulation, emphasizing the significance of considering temporal and spatial factors for effectiveness. Effective communication, characterized by clear and appropriate messaging, is key to achieving these objectives. The primary research focus is on the "Village Film Festival," particularly the creation and competition of short documentary drama (docudrama) films by the local community, serving as a medium for communication and persuasion through audio-visual storytelling. The study reveals that communication strategies play a pivotal role in achieving these goals, with the festival successfully disseminating messages and engaging viewers to contemplate and interact with the content. As a suggestion, future endeavors in public policy and communication should actively employ communication strategies, leveraging audio-visual storytelling, such as docudrama films, to address global challenges, enhance product quality, and promote community cohesion, drawing insights from this research as a noteworthy case study demonstrating their potential impact.